On the HOMA index of some acyclic and conducting systems1. Issue 13 (14th February 2015) - Dobrowolski, Jan Cz.; Ostrowski, Sławomir
<x xml:space="preserve">Abstract</x> The HOMA index can be useful for acyclic linear systems and design of new conducting polymers.